Photovoice and Health Perception in a Group of Early-Career Nurses - Jakub Lickiewicz; Bettina Kolb; Jadwiga Piątek; Laura S. Lorenz (MDPI AG, 2024)
Background. Nurses' perceptions of health are essential to decision making and communicating with clients. However, little is known about their own perceptions of this phenomenon. This study focuses on health-related beliefs among young nurses enrolled in a master's-level nursing program using a modified photovoice methodology. Methods. The study population was 87 nurses undergoing a master's degree in nursing at Jagiellonian University Medical College in Krakow, Poland, participating in an obligatory health psychology course. For the modified photovoice activity, the participants took three photos related to their perceptions of (1) health, (2) health protective factors, and (3) health risk factors. The data interpretation involved a thematic analysis of these photos and captions; a narrative analysis to distinguish between documentary and symbolic photos; and a descriptive analysis of the photo production. Results. Eighty-seven students completed the photography assignment. The mean age was 22.1 years (SD = 1.1). Most photos (91%) documented real-life health behaviours. Some photos (9%) used everyday objects such as sunflowers to create symbols related to health. A photo series showed a model of the human brain in different environments and activities. Conclusions. Student participation in the photovoice activity appeared to strengthen observation and interpretation skills, which are essential to client care. Students used this opportunity to reflect on their own lives and environments and show their perceptions of health, health protective factors, and health risks. The activity planted seeds for changes in students' health perceptions and critical thinking. Future research could explore whether participation in a modified photovoice activity as experiential learning in a required health psychology course contributes to changes in master's-level nursing students' personal health behaviours and client care.